Кот Котофеич: 6+ / перевод с удмуртского В. Н. Ившина, В. И. Емельянова - Бронникова А. А. (Сказки для малышей, 2016)
Экземпляры: ф. 1 (20160517) / Инвентарный номер: 104326 / Цена: 100.00 / Авт.знак: К 73 / ГРНТИ: 17.71 / ББК: 82.3(2Рос=Удм)